Innovative Analytical Profiling of Lakshadi Anjana Drops: Physico-Chemical, Microbiological, and Organoleptic Insights for Therapeutic Applications - P Nair, Praveena; Pritam Keskar, Manjiri (Journal of Neonatal Surgery, 2025)
Introduction: Lakshadi Anjana Drops, an Ayurvedic ocular formulation, is designed to alleviate eye-related conditions with its unique blend of traditional herbal ingredients. This study aimed to evaluate the formulation's quality, safety, and efficacy through comprehensive physicochemical, microbiological, and HPTLC analysis. Methods: The formulation underwent physico-chemical analysis to determine parameters such as pH, refractive index, peroxide value, saponification value, and iodine value. Microbiological assessments included total microbial and bacterial counts, as well as the detection of specific pathogens (E. coli, Salmonella, and S. aureus). HPTLC profiling was performed to identify and validate the phytoconstituents. Organoleptic characteristics were also evaluated, including color, odor, taste, and consistency. Results: The pH of the formulation was 7.82, suitable for ocular application. The refractive index and other physico-chemical parameters, including peroxide value (2.18 meq/kg), saponification value (210), and iodine value (38.49), were within acceptable ranges, indicating chemical stability. Microbiological analysis revealed total microbial, bacterial, and fungal counts within permissible limits. Specific pathogens, including E. coli, Salmonella, and S. aureus, were absent. HPTLC profiling demonstrated clear and distinct phytochemical bands, confirming the presence of active constituents and the purity of the formulation. Organoleptic evaluation showed that the formulation was black, semi-liquid, and pleasant in odor and taste. Conclusion: Lakshadi Anjana Drops showed strong physico-chemical stability, microbiological safety, and phytochemical integrity, affirming its suitability for ocular use. By combining Ayurvedic tradition with modern analysis, the formulation highlights its therapeutic potential and opens avenues for broader clinical applications.